The methods of Lanna proverb variations used among three generations in Chiang Saen District, Chiang Rai province - บุญเคลือบ, วิไลลักษณ์ (Journal of Liberal Arts Prince of Songkla University, 2025)
This research examined the methods of Lanna proverbs variation used among three generations of people in Chiang Saen District, Chiang Rai Province. The research sample group consisted of 90 informants from three generations, 30 informants per generation: aged 55-70 years; 35-50 years; and 15-30 years, from six sub-districts, namely, Yonok, Mae Ngern, Sridonmoon, Wiang, Pasak and Baan Saew. Data was collected through conducting interviews, and the data set was analyzed statistically in terms of frequency distribution, percentage and descriptive analysis. The qualitative data were obtained through Lanna proverbs variation in twenty Lanna proverbs. Based on the result, five types of Lanna proverbs variation were found, including syllable omission, syllable addition, word replacement, using standard Thai language and changing vocabulary. However, the three most significant categories of Lanna proverbs variation found were changing vocabulary, syllable omission and syllable addition. Particularly, the variation in the Lanna proverbs occurred most frequently among the 1st generation, 2nd and 3rd generation, respectively.